(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Eighteen soybean genotypes were evaluated for resistance to pod shattering and other important agronomic traits in 2016 dry season at the screen house of Institute for Agriculture Research Samaru, Ahmadu Bello University, Zaria Nigeria. Four genotypes with glabrous leaf were susceptible to pod shattering. In the same vein, three genotypes with leaf glabrous were moderately resistant. All genotypes with leaf pubescence were either highly resistance or resistance to pod shattering. The mean square from the analysis of variance for the nine traits measured indicated that seven traits showed highly significant differences (P<0.01) among the genotypes, while significant difference was observed for pod length (P<0.05), however number of seed per pod showed no significant difference among all genotypes. The correlation analysis indicated that there was positive correlation between pod shattering and days to maturity (r = 0.346*); however there was negative correlations between number of seeds per pod and shattering score (r = -0.527**). A negative correlation also, existed between number of pod per plant and pod shattering (r=-0.403*), while plant height and pod shattering showed a positive correlation (0.334*). In the same vein, plant height had negatively correlated with 100 seed weight (r = -0.488**), but positively correlated with days to flowering (r = 0.359*).